Top ten global justice law review articles, 2008 - Guiora, Amos N., 1957- (Oceana : Oxford University Press, 2009)
Top Ten Global Justice Law Review Articles 2008 is a thorough and accessible review of the most salient, the most controversial, and the most illuminating essays on security law in the previous calendar year. In this edition, Professor Amos Guiora presents the ten most vital and pertinent law review articles from 2008 written by both scholars who have already gained international prominence as experts in global justice as well as emerging voices in the realm of international criminal law and human rights. These articles deal with issues of terrorism, security law, environmental law, and the preservation of civil liberties in the post-9/11 world. The chosen selections derive not just from the high quality and expertise of the articles' authors, but equally from the wide diversity of legal issues addressed by those authors. Guiora combines the expertise of scholars from both eminent law schools and government agencies to provide a valuable resource for scholars and experts researching this important subject area. This annual review provides researchers with more than just an authoritative discussion on the most prominent global justice debates of the day; it also educates researchers on new issues that have received far too little attention in the press and in academia. These expert scholars and leaders tackle and give voice to issues that range from the psychology of terrorism to the role of oil in the Sudanese genocide to the oppression of women in new Arab democracies to transnational environmental cooperation and beyond. Together, the vast knowledge and independent viewpoints represented by these ten authors make this volume, a valuable resource for individuals new to the realm of global justice and for advanced researchers with a sophisticated understanding of the field. Top Ten Global Justice Law Review Articles 2008 serves as a one-stop guidebook on how both the U.S. and the world generally are currently grappling with fundamental principles of social and political life.
Keywords: Terrorism -- Prevention -- Government policy.; National security -- Law and legislation.; Intelligence service -- Law and legislation.; Terrorism -- Prevention -- Law and legislation.; Terrorisme -- Prévention -- Politique gouvernementale.; LAW -- Jurisprudence.; LAW -- General Practice.; LAW -- Reference.; LAW -- Essays.; LAW -- Paralegals & Paralegalism.; LAW -- Practical Guides.; Intelligence service -- Law and legislation; National security -- Law and legislation; Terrorism -- Prevention -- Government policy; Terrorism -- Prevention -- Law and legislation; Electronic book.